Jesuit philosophy on the eve of modernity - Casalini, Cristiano 1976- (Colección de libros electrónicos de ULoyola, 2019)
In Jesuit Philosophy on the Eve of Modernity Cristiano Casalini collects eighteen contributions by renowned specialists to track the existence and distinctiveness of Jesuit philosophy during the first century since the inception of the order.